The patient journey of newly arrived asylum seekers and responsiveness of care: a qualitative study in Germany - Biddle, Louise; Ziegler, Sandra; Baron, Jenny; Flory, Lea; Bozorgmehr, Kayvan (PLOS ONE, 2022)
Background Research on health and healthcare for asylum seekers and refugees (ASR) has focused strongly on accessibility and legal entitlements, with quality of care receiving little attention. This study aimed to assess responsiveness, as non-medical quality of care, in the narratives of ASR patients recently arrived in Germany. Methods 31 ASR with existing medical conditions were recruited in six refugee reception centres and three psychosocial centres. Semi-structured, qualitative interviews were conducted which reconstructed their patient journey after arrival in Germany. Interviews were recorded, transcribed verbatim and evaluated using thematic analysis. Results The experiences of participants throughout the patient journey provided a rich and varied description of the responsiveness of health services. Some dimensions of responsiveness, including respectful treatment, clear communication and trust, resurfaced throughout the narratives. These factors were prominent reasons for positive evaluations of the health system, and negative experiences were reported in their absence. Other dimensions, including cleanliness of facilities, autonomy of decision-making and choice of provider were raised seldomly. Positive experiences in Germany were often set in contrast to negative experiences in the participants’ countries of origin or during transit. Furthermore, many participants evaluated their experience with healthcare services in terms of the perceived technical quality of medical care rather than with reference to responsiveness. Conclusion This qualitative study among ASR analysed patient experiences to better understand responsiveness of care for this population. While our results show high overall satisfaction with health services in Germany, using the lens of responsiveness allowed us to identify particular policy areas where care can be strengthened further. These include in particular the expansion of high-quality interpreting services, provision of professional training to increase the competency of healthcare staff in caring for a diverse patient population, as well as an alignment between healthcare and asylum processes to promote continuity of care.